ChemInform Abstract: An Efficient Cyanosilylation of Aldehydes with Trimethylsilyl Cyanide Catalyzed by MgI2 Etherate. Issue 10 (7th March 2013) - Wang, Yanping; Feng, Meiling; Liu, Yingshuai; Zhang, Xingxian
Abstract Various aliphatic and aromatic aldehydes produce the desired cyanohydrin products with good to excellent yields.